Neuroinflamação e via apoptótica na epilepsia - Kegler, Aline (2015)
Epilepsy is a neurological disease that affects around 1% of world population, with neurobiological, neurochemical, cognitive and psychological consequences. Despite the good prognosis, the high number of epilepsy patients who have refractory seizures to medicine, reflects lack of a better understanding about excitotoxic disorders characteristic of the disease. So, the aim of the study was to investigate if there is an association between apoptotic markers and inflammation pathway in epileptic subjects and those without the disease. Blood samples were collected from subjects with epilepsy and were measured protein carbonyl, tumor necrosis factor alpha (TNF-α), interferon gamma (IFN-لا), acetylcholinesterase (AChE), caspases (CASP8 and CASP3) and picogreen (PG). The results showed an increase in all analyzed biochemistry parameters from epilepsy subjects when compared to healthy, suggesting that there is a relation between this disease with apoptotic and inflammatory markers. Furthermore, there was a positive correlation between TNF-α with CASP 8 and 3. IFN-لا was just correlated with caspase 3. The correlation between analyzed parameters with seizure severity and antiepileptic drugs (AEDs) treatment was not significant, indicating that medicine administration and symptoms improve did not influence obtained results. So, our results suggest that epileptic seizures can induce the creation of a vicious circle between neuroinflammation and cell death, resulting in DNA damage in epilepsy patients. Furthermore, we suggest that AEDs acting in TNF-α or IFN-لا pathway could represent an adjunctive therapy in epilepsy patients treatment.